Character-Based English Language Education Model in the Era of Digital Transformation - Romdanih Romdanih; Yuliwati Yuliwati; Lutfi Hardiyanto (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study aims to formulate and develop a conceptual model of character-based English language education in the era of digital transformation (CBELT-DT). A systematic and rigorous research approach was adopted through a Systematic Literature Review (SLR), adhering to the PRISMA 2020 protocol and SPAR-4-SLR framework, to ensure transparency and replicability in synthesizing the literature. The research was conducted using a Systematic Literature Review (SLR) approach on 25 articles published between 2020 and 2025, sourced from Google Scholar, Scopus, and DOAJ. The inclusion criteria focused on the integration of character education, digital literacy, and instructional innovation within English language teaching contexts. Thematic analysis identified five main themes: the integration of character values in English language learning, the reinforcement of digital literacy and ethics, media and instructional technology innovation, the development of intercultural competence, and the philosophical and cultural foundations of character education. The findings indicate that the CBELT-DT model emphasizes synergy between teacher readiness, technology-based instructional strategies, the internalization of character values, and reflective evaluation. This model is rooted in local values with a global orientation and is relevant for strengthening students’ academic competence, digital ethics, and identity. The study contributes to curriculum development, teacher capacity building, and the formulation of adaptive educational policies in response to the challenges of the digital era. Further research is recommended for empirical testing of the CBELT-DT model and the development of valid digital character assessment instruments. These findings underscore the urgency of integrating character education, digital literacy, and global competence into English language learning as a strategic response to the dynamics of 21st-century education.